One Lesson Learned: Frame Language Processing—Literal and Figurative—as a Human Brain Function. - Kutas, Marta (Metaphor & Symbol, 2006)
What research is conducted on language processing and how that research is conducted are largely determined by researchers' assumptions about the functional organization of mental processes. These have changed significantly since the 1970s when the brain's role in language processing—although acknowledged—was practically inconsequential to psycholinguistic research or theory; this change is due in large part to considerable growth in knowledge of brain structure and function. I argue that when language is properly appreciated as one brain function among many, psycholinguistics will benefit from heeding certain factors that have received proportionately little attention within mainstream psycholinguistic research: (a) the hemispheres; (b) time and timing; (c) context liberally construed to include, for example, personality traits and mood; and (d) individual differences as a proxy for experience. I conclude with why it has not been so easy to answer such fundamental questions as where in the brain language is localized, and how activation of these language areas leads to understanding. The main message is that researchers of nonliteral language processing can benefit from the significant progress in the neurosciences in the past few decades more by thinking of language as brain function and as an experience than by viewing it merely as the (localizable) seat of nonliteral language. I recommend actively and seriously incorporating brain principles into thinking about all language processes and how best to investigate them.